THE INFLUENCE OF LECTURER COMPETENCE, TEACHING STYLE, AND WORK CULTURE ON STUDENT PREFERENCES IN THE ACCOUNTING PROFESSION - Asep Suherman; Indrianingsih Indrianingsih; Yusuf Yusuf (SEAN Institute, 2022)
The purpose of the study was to examine and analyze the effect of lecturer competence, teaching style and work culture on student preferences for the accounting profession. with a structural equation model with the SmartPLS 3.0 analisa analysis tools. The results showed that lecturer competence, teaching style and work culture had no effect on student preferences for the accounting profession. Based on the research findings, the factors that cause lecturers are not knowing each student, lecturers are not aware of students' academic problems, lecturers are not firm in giving sanctions/punishments for students who violate regulations, lecturers do not become inspiration for a career as accountants and the environment does not encourage being accountants